Deconstructing the role of the ECM microenvironment on drug efficacy targeting MAPK signaling in a pre-clinical platform for cutaneous melanoma. (July 2015) - Blehm, Benjamin H.; Jiang, Nancy; Kotobuki, Yorihisa; Tanner, Kandice
Abstract: Therapeutics targeting the BRAF kinase in cutaneous melanoma have significantly improved patient survival. However, durable responses in the face of metastatic disease are rarely realized where the problem of brain metastases is generally growing in magnitude. Tumor and stromal cells dynamically remodel the extracellular matrix (ECM) during the establishment of a metastatic lesion. We reasoned that ECM composition strongly determines drug efficacy on cell motility, adhesion and viability rendering one drug more potent and another less so. To test this hypothesis, we constructed platforms recreating the ECM composition due to the stroma and tumor cells, mimicking the brain's perivascular niche and hyaluronic acid (HA) rich parenchyma. Using human melanoma cell lines, we observed that cell adhesion was minimally affected by BRAF inhibition but ablated by ERK inhibition. Cell motility was impaired for both drugs. We determined that the composition and architecture of the ECM niche modulated drug efficacy. In one series, potency of BRAF inhibition was blunted in 3D Fibronectin-HA hydrogels whereas Laminin-HA hydrogels protected against ERK inhibition. In the other series, Laminin blunted drug efficacy, despite both series sharing the same BRAF mutation. These data reinforce the importance of contextual drug assessment in designing future therapeutics.